An increasing opine carbon bias in artificial exudation systems and genetically modified plant rhizospheres leads to an increasing reshaping of bacterial populations. Issue 19 (October 2014) - Mondy, Samuel; Lenglet, Aurore; Beury‐Cirou, Amelie; Libanga, Celestin; Ratet, Pascal; Faure, Denis; Dessaux, Yves
Abstract To investigate how exudation shapes root‐associated bacterial populations, transgenic Arabidopsis thaliana plants that exuded the xenotopic compound octopine at low and high rates were grown in a nonsterile soil. Enumerations of both cultivable and octopine‐degrading bacteria demonstrated that the ratios of octopine degraders increased along with octopine concentration. An artificial exudation system was also set up in which octopine was brought at four ratios. The density of octopine‐degrading bacteria directly correlated with the input of octopine. Bacterial diversity was analysed by rrs amplicon pyrosequencing. Ensifer and Pseudomonas were significantly more frequently detected in soil amended with artificial exudates. However, the density of Pseudomonas increased as a response to carbon supplementation while that of Ensifer only correlated with octopine concentrations possibly in relation to two opposed colonization strategies of rhizosphere bacteria, that is, copiotrophy and oligotrophy.